Kebijakan Progam Kampus Mengajar: Antara Cita Dan Fakta - Nafis Abqori Fadli; Farid Setiawan; Iffatur Rohmah; Herpin Nurgiansyah; Rahma Sari; Iffah Nurhasanah; Hanafi Nurhuda Avicena (Jurnal Ilmiah Wahana Pendidikan, 2022)
The teaching campus is one of the government programs from the policy of the Independent Learning Program-Independent Campus (MBKM) which was initiated directly by the Ministry of Education and Culture which provides opportunities for students to help teachers and principals at the elementary and junior high levels in holding learning activities affected by the pandemic.. In the context of learning on campus policy teaching is actually more directed at providing more opportunities for humans to master various disciplines. This research was conducted using library research so that the method used in this research is literature study. Data collection techniques in this study used secondary data, namely by collecting relevant data from books, scientific journals, articles and so on. Through this program, students can devote their knowledge, skills, and inspire these elementary and middle school students to broaden their goals and horizons.